Tetranychus (T.) urticae KOCH, 1836 (ACARI), PRAGA SEVERA DE ORQUÃDEAS (Catasetum SP.) EM RIPADOS - Flechtmann, Carlos H. W. (REVISTA DE AGRICULTURA, 2016)
Tetranychus (T.) urticae KOCH, 1836 (ACARI), PRAGA SEVERA DE ORQUÃDEAS (Catasetum SP.) EM RIPADOS